A medical costs study of older patients with acute myocardial infarction and metabolic syndrome in hospital - Fan GQ (Dove Medical Press, 2015)
Guan-qi Fan,1 Kai-li Fu,1 Cheng-wei Jin,1 Xiao-zhen Wang,2 Lu Han,1 Hui Wang,1 Ming Zhong,1 Yun Zhang,1 Wei Zhang,1 Zhi-hao Wang1,3 1Key Laboratory of Cardiovascular Remodeling and Function Research, Chinese Ministry of Education and Chinese Ministry of Public Health, Department of Cardiology, Qilu Hospital of Shandong University, 2Shandong University of Traditional Chinese Medicine, 3Department of Geriatric Medicine, Qilu Hospital of Shandong University, Ji’nan, People’s Republic of China Background: Older patients with acute myocardial infarction (AMI) usually have a poor prognosis, but whether this poor prognosis leads to high hospital costs remains unclear. This study investigated the clinical outcomes of and costs incurred by older patients with AMI and metabolic syndrome (MS) in hospital.Methods and results: Patients with AMI seen at Qilu Hospital of Shandong University between January 2011 and May 2013 were separated into four groups: young non-MS patients (n=282), older non-MS patients (n=324), young MS patients (n=217), and older MS patients (n=174). We found that advanced age was significantly associated with worse clinical outcomes, and that the clinical outcomes in patients with AMI and MS are also worsened. At the same cost (RMB¥10,000), older patients with and without MS had a markedly increased number of cardiovascular incidences compared with younger patients without MS. In a comparison of the incremental cost-effectiveness ratio (ICER) of percutaneous coronary intervention, older patients without MS had a lower ICER for cardiovascular incidences and a higher ICER for cardiac event-free survival rate when compared with young patients without MS, but a lower ICER for cardiovascular incidences and a higher ICER for cardiac event-free survival rate when compared with older MS patients. Conclusion: Older AMI patients have poor clinical outcomes and their treatment is not cost-effective; however, the results are worse in patients with AMI and MS. Percutaneous coronary intervention is a cost-effective therapy in older patients with AMI, but its cost-effectiveness decreases in patients with AMI and MS. Keywords: metabolic syndrome, aging, vascular, acute myocardial infarction, cost-effectiveness